Handheld Portable Potato Cutting Machine - Anuarizul, Muhammad Hafiz Haiqal; Wagiman, Abdullah; Abdul A'lim, Arif Haikal; Ibrahim, Muhammad Aqif (Multidisciplinary Applied Research and Innovation, 2022)
A potato cutting machine was once very prevalent, particularly in the food industries. The machine will be described as a large device that is not suitable for domestic use based on these statements. This project was born out of a need to address the issue while also easing the strain on the home and possibly assisting the small vendor community. The project focuses on tiny and medium-sized potatoes, as well as a portable and low-cost fabrication machine that may be employed in households and small businesses. The machine's functionality was tested, and the results were compared to manual methods. For the purposes of comparison, the machine is estimated can cut potatoes in up to 62 percent less time. This compact item will not take up any space in the kitchen during the renovation. Finally, this product greatly aids the community in producing their own homemade potato chips using their own recipes and patterns.